2023
DOI: 10.1097/jxx.0000000000000899
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner educational preparation and confidence related to managing antipsychotic medications and associated drug-induced movement disorders

Abstract: Background:Antipsychotic medications (APMs) have been used to treat multiple psychiatric disorders for decades. The conditions to use these medications have expanded from primarily psychotic disorders to Food and Drug Administration–approved uses as first-line mood stabilizers in bipolar disorder and adjunctive pharmacotherapy in unipolar depression. Antipsychotic medications can have serious side effects, including drug-induced movement disorders (DIMDs). Nurse practitioners (NPs) in non–psychiatric-mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…It is important to note that pharmacological treatments for DIMDs should be carefully considered and monitored by a healthcare professional [128]. The choice of medication, dose, and duration of therapy should be tailored to the individual's specific needs and circumstances.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…It is important to note that pharmacological treatments for DIMDs should be carefully considered and monitored by a healthcare professional [128]. The choice of medication, dose, and duration of therapy should be tailored to the individual's specific needs and circumstances.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…DIP was recognized in the early 1950s with antipsychotic drugs. It was reported that DIP occurs during the initial period of antipsychotic medication exposure [ 55 ]. The pathophysiology of DIP is related to disruptions in the basal ganglia motor pathways secondary to dopaminergic receptor blockade [ 56 ].…”
Section: Parkinsonismmentioning
confidence: 99%